"Os desafios de uma estudante-estagiária de Educação Física" - Raquel Dias Correia (2021)
This document aims to portray and reflect, in a critical and supported way, the entire teaching and learning process that took place during the school placement in a School from Porto area at the academic school year 2019/20. This is the end of an initial cycle of studies aimed at building a professional identity, and this is the first moment of action. The school placement was held in a private institution with a group of three preservice teachers and the guidance and supervision of a university teacher and a cooperating teacher. The organization of this document by chapters is: 1) Introduction; 2) Personal Framework, which contextualizes my path and expectations for the challenge; 3) Institutional Framework, which reports the framework of the school placement and school as well as the characterization of school contexts lived; 4) Operational Framework, which reflects the work developed throughout the school year. This chapter is subdivided into two areas: Area 1: Organization and Management of Teaching and Learning, refers to the practical realization, reflecting on the difficulties and challenges faced as well as the strategies used; Area 2: School Participation and Community Relationship, which depicts the activities that occurred throughout the internship. Finally, 5) conclusion, where I reflect on the process and the stage path.